curricular management from the vision of the teacher as a curriculum builder (Revista Electrónica REDINE, 2018)
This article shows theoretical-methodological tools to manage the curriculum from the constructions proposed by teachers to dynamize and articulate their pedagogical practice with the needs of their educational context. Emerges as a finding of the research on teaching in primary education, a study that was assumed under the principles of the interpretive paradigm from the qualitative perspective, which made possible the understanding of the phenomenon of study from the meanings and meanings shared by the versions themselves. . It was obtained as a methodological theoretical approach that curricular management from the view of the teacher as a curriculum builder is a systematic process of integration within the educational institutions, aimed at focusing efforts with the actors of the educational community to reconstruct a set of theoretical postulates in the educational action, with a view to stimulating the formative processes in order to establish new meanings and meanings to education.